Quản lí hoạt động chuyển đổi số trong dạy học tại các trường trung học cơ sở khu vực phía Tây tỉnh Gia Lai: Thực trạng và giải pháp - Đào Thị Phương Mai, Đào Thị Phương Mai; Nguyễn Sỹ Thư, Nguyễn Sỹ Thư (Tạp chí Giáo dục, 2026)
In the context of educational digital transformation, this study investigates the current situation and proposes management solutions for digital transformation in teaching and learning at lower secondary schools in several wards in the western area of Gia Lai Province using a three-layer model. A survey of 221 school leaders and teachers from ten schools indicates that digital transformation has been implemented relatively effectively, particularly in developing digital competence among teachers and students; however, limitations remain regarding infrastructure, equipment, and the digital competence of a proportion of teachers and parents. Based on these findings, the paper proposes three groups of solutions: enhancing digital competence among relevant stakeholders; improving facilities, innovating professional training, and providing learning devices; and integrating software systems while innovating teaching practices and online assessment. The results provide practical evidence to inform educational management in the national digital transformation process.